From basalt to biosphere: Early non-vent community succession on the erupting Vailulu’u deep seamount - Herrera, Santiago; Chadwick, William W.; Jackson, Matthew G.; Konter, Jasper; McCartin, Luke; Pittoors, Nicole; Bushta, Emily; Merle, Susan G. (Frontiers in Marine Science, 2023)
Volcanic eruptions provide rare opportunities to witness the biological recolonization of areas covered by new lava flows by effectively resetting the ecological succession clock to zero. The role of submarine volcanic eruptions as disturbance events and the resulting patterns of ecological succession have mainly been studied in hydrothermal vent ecosystems. However, the effects of submarine volcanic eruptions as disturbance forces have rarely been studied in non-vent ecosystems, particularly on seamounts. Here, we document the early stages of ecological succession of non-vent benthic communities inhabiting the summit caldera of the active Vailulu’u submarine volcano in American Samoa. Sitting above the Samoan volcanic hotspot, Vailulu’u is the youngest volcano of the Samoan chain. Repeated mapping of Vailulu’u in 1999, 2005, 2006, 2012, and 2017 revealed the progressive growth of a new cone named Nafanua. In 18 years, the cone grew >300 meters in height from a starting depth of ~1000 meters below sea level (mbsl). The differential analyses of this time-series bathymetry dataset enabled the assignment of maximum age ranges to different portions of the new cone. High-definition ROV imagery collected in 2017 revealed patterns of community structuring consistent with ecological succession: newly erupted seafloor contained a subset of the benthic species found on older seafloor. Furthermore, individual animal sizes in the younger seafloor zones were smaller than in the older zones. This unusual interdisciplinary combination of geological and biological observations provides constraints on which deep-sea animals recolonize new seafloor after a major disturbance event and how quickly. This knowledge could be applied to identify signs and states of recovery from anthropogenic disturbances by a deep seamount ecosystem.